2016
DOI: 10.1177/0022034516656787
|View full text |Cite
|
Sign up to set email alerts
|

Full Spectrum of Postnatal Tooth Phenotypes in a Novel Irf6 Cleft Lip Model

Abstract: Clefting of the lip, with or without palatal involvement (CLP), is associated with a higher incidence of developmental tooth abnormalities, including hypodontia and supernumerary teeth, aberrant crown and root morphologies, and enamel defects, although the underlying mechanistic link is poorly understood. As most CLP genes are expressed throughout the oral epithelium, the authors hypothesized that the expression of CLP genes may persist in the dental epithelium and thus, in addition to their earlier role in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 40 publications
2
39
2
Order By: Relevance
“…This interaction masks the receptor binding sites on GDF11 (Walker et al, 2017). Homozygous Fst knockout mice exhibit cleft palate, whereas Keratin14-driven epithelial-specific conditional knockout of the gene shows altered tooth cusp morphology and delayed third molar development in mice, similar to that reported for the major CL/P gene, Irf6 (Blackburn et al, 2012;Chu et al, 2016).…”
Section: Discussionsupporting
confidence: 62%
“…This interaction masks the receptor binding sites on GDF11 (Walker et al, 2017). Homozygous Fst knockout mice exhibit cleft palate, whereas Keratin14-driven epithelial-specific conditional knockout of the gene shows altered tooth cusp morphology and delayed third molar development in mice, similar to that reported for the major CL/P gene, Irf6 (Blackburn et al, 2012;Chu et al, 2016).…”
Section: Discussionsupporting
confidence: 62%
“…In the absence of Irf6 , mice exhibit severe cutaneous, limb, and orofacial defects and are perinatal lethal . Salivary glands and dental development are also altered in these mice, supporting a major role for IRF6 in craniofacial development. In humans, mutations in IRF6 cause Van der Woude syndrome (VWS, OMIM 119300) and popliteal pterygium syndrome (PPS, OMIM 119500) .…”
Section: Introductionmentioning
confidence: 90%
“…This hypothesis is based on the following: (1) In this study, we observed no or incomplete recombination with the EIIa‐Cre “deleter strain,” and with two other tissue specific Cre transgenes, including K14‐Cre‐ER (Vasioukhin, Degenstein, Wise, & Fuchs, ) and Tgfb3‐Cre (Yang, Li, & Kaartinen, ; data not shown). (2), A previous study used this Irf6 fl allele to examine the role of Irf6 in dental epithelium, using the Pitx2‐Cre transgene (Chu et al, ). While the Pitx2‐Cre driver was previously shown to be competent to knockout other genes in oral epithelium that were required for palatogenesis (He et al ., ; Xiong et al ., ) , and Irf6 function in oral epithelium is required for palatogenesis (Ingraham et al, ; Richardson, Dixon, Jiang, & Dixon, ), no pathology was observed during palatogenesis (Chu et al, ).…”
Section: Resultsmentioning
confidence: 99%